PENGARUH BIMBINGAN BELAJAR DI LUAR SEKOLAH TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN SEKECAMATAN PEJAGOAN TAHUN AJARAN 2019/2020 - Siti Rahmawati; Joharman Joharman; Ngatman Ngatman (Universitas Sebelas Maret, 2020)
Abstract: The study aimed to prove the difference between students taking tuition and students who did not take tuition on mathematics learning outcomes of fourth grade students in public elementary schools at Pejagoan sub-district in academic year of 2019/2020. The research was quantitative comparative method. Type of sampling was cluster random sampling technique with the help of Statistical Product and Service Solution (SPSS) version 16. The samples were 263 students in ten public elementary schools at Pejagoan sub-district. Data analysis used independent sample t-test, with a significance level of 0.05. In the test of homogeneity, the result was sig = 0,000 (sig < 0.05). It meant that there was significant difference between students taking tuition and students who did not take tuition on mathematics learning outcomes. The data of student mathematics learning outcomes was homogeneous.